High genetic differentiation within the Hemidactylus turcicus complex (Reptilia: Gekkonidae) in the Levant, with comments on the phylogeny and systematics of the genus - Moravec, Jiří; Kratochvíl, Lukáš; Amr, Zuair S.; Jandzik, David; Šmíd, Jiří; Gvoždík, Václav (Zootaxa, 2011)
The molecular phylogeny of Hemidactylus turcicus (sensu lato) and related Levantine taxa of Hemidactylus geckos were studied using mitochondrial DNA sequence data. Five main phylogenetic lineages were detected within the distribution area of H. turcicus: (1) H. turcicus (sensu stricto) from the Mediterranean region comprising two widely distributed haplotype groups divergent by 2.1%; (2) H. cf. turcicus from north-eastern Israel forming a divergent (7.2%) sister lineage to H. turcicus s.s.; (3) H. turcicus lavadeserticus from the black Syrian basalt desert; (4) H. mindiae from southern Jordan; and (5) a highly supported lineage representing an unnamed species of Hemidactylus distributed in southern Syria and Jordan. On the basis of the obtained phylogenies, genetic divergences and morphological comparisons, the subspecies H. turcicus lavadeserticus is elevated to full species level and the unnamed Hemidactylus clade is described as a new species, H. dawudazraqi sp. n. In addition, an unnamed lineage of Hemidactylus from southern Sinai and exceptional genetic differentiation within “H. turcicus-like” forms from Yemen are reported, the type locality of H. turcicus is discussed and also comments are provided on the phylogeny and systematics of the genus Hemidactylus.